Strategic Commitment Versus Flexibility in a Duopoloy with Entry and Exit - Jeffery Ely; Johannes Horner; Wojciech Olszewski (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2004)
We introduce a class of strategies which generalizes examples constructed in two-player games under imperfect private monitoring. A sequential equilibrium is belief-free if, after every private history, each player.s continuation strategy is optimal independently of his belief about his opponents. private histories. We provide a simple and sharp characterization of equililibrium payos using those strategies. While such strategies have desirable robustness properties, they are not rich enough to generate a folk theorem in most games besides the prisoner's dilemma, even when noise vanishes.
Keywords: 330